Faktor Penyebab Stres Pada Perawat di Rumah Sakit Jiwa: Literatur Review - Patricia Putri Carenina Manuk Dewa; Christin Paula Lede; Priskila Amelia Takalapeta; Lusia Anggriani Leba (Journal of Creative Student Research, 2024)
Stress is a reality of everyday life that we cannot avoid. All professionals in hospitals are at risk of stress, but nurses have a higher level of stress. High levels of job stress also affect the performance, satisfaction, productivity, and caring behavior of nurses towards patients will be lower. Nurses are required to work skillfully, make decisions quickly, and precisely so that nurses can experience stress, which in turn can make nurses lose motivation, experience boredom which leads to decreased work performance and deteriorating patient care. This literature review aims to determine the various factors that cause stress in nurses in mental hospitals. The literature review used in writing this literature review is by searching for national literature using databases such as Google Scholar, or other search engines. At the beginning of the search with keywords: "Stress","Nurse," "Mental Hospital" the journals obtained were more than 968,000 articles, after being filtered by looking at the inclusion criteria, 5 national articles were obtained from the 2017-2023 timeframe. The inclusion criteria for selecting literature review studies are that this research must provide information about the factors that cause stress in nurses in mental hospitals. Exclusion criteria, the main focus of this literature review is the factors that cause stress in nurses in mental hospitals. Based on 5 artikel that have been reviewed, it is found that work stress in nurses in mental hospitals is caused by various interrelated factors, such as excessive workload, emotional demands, poor work relationships, lack of social support, and unpleasant work environment.